DIGITAL TECHNOLOGIES FOR OPTIMIZATION: REDUCE COSTS AND INCREASE PROFIT - Nasirov Abbasovich, Ilkham (THE INNOVATION ECONOMY, 2025)
The article examines the use of digital technologies to optimize business processes in Uzbekistan. It considers ways to reduce costs and increase profits, analyzes current trends and successful cases, and offers practical recommendations for enterprises in the context of digital transformation.